A radical switch in clonality reveals a stem cell niche in the epiphyseal growth plate - Newton, Phillip T; Li, Lei; Zhou, Baoyi; Schweingruber, Christoph; Hovorakova, Maria; Xie, Meng; Sun, Xiaoyan; Sandhow, Lakshmi; Artemov, Artem V; Ivashkin, Evgeny; Suter, Simon; Dyachuk, Vyacheslav; et al. (Nature, 2019)
Longitudinal bone growth in children is sustained by growth plates, narrow discs of cartilage that provide a continuous supply of chondrocytes for endochondral ossification1. However, it remains unknown how this supply is maintained throughout childhood growth. Chondroprogenitors in the resting zone are thought to be gradually consumed as they supply cells for longitudinal growth1,2, but this model has never been proved. Here, using clonal genetic tracing with multicolour reporters and functional perturbations, we demonstrate that longitudinal growth during the fetal and neonatal periods involves depletion of chondroprogenitors, whereas later in life, coinciding with the formation of the secondary ossification centre, chondroprogenitors acquire the capacity for self-renewal, resulting in the formation of large, stable monoclonal columns of chondrocytes. Simultaneously, chondroprogenitors begin to express stem cell markers and undergo symmetric cell division. Regulation of the pool of self-renewing progenitors involves the hedgehog and mammalian target of rapamycin complex 1 (mTORC1) signalling pathways. Our findings indicate that a stem cell niche develops postnatally in the epiphyseal growth plate, which provides a continuous supply of chondrocytes over a prolonged period.
Keywords: Mechanistic Target of Rapamycin Complex 1; Chondrocytes; buněčné klony; nika kmenových buněk; Aging; Growth Plate; Cell Self Renewal; Stem Cell Niche; růstová ploténka; mužské pohlaví; Mice; chondrocyty; Cartilage; stárnutí; ženské pohlaví; zvířata; mTORC1; buněčná sebeobnova; chrupavka; myši; Clone Cells; Female; Male; Animals